2009
DOI: 10.7326/0003-4819-150-3-200902030-00005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Immunochemical Fecal Occult Blood Tests for Colorectal Adenoma Detection

Abstract: The German Research Foundation (Deutsche Forschungsgemeinschaft) within the framework of a PhD program (Graduiertenkolleg 793).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
204
3
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(241 citation statements)
references
References 21 publications
8
204
3
17
Order By: Relevance
“…These studies have used different types of FIT. This hampers a direct comparison of test results because the different types of FIT are known to vary considerably in sensitivity, from 25% to 72%, within the same population (8). Overall, the sensitivity of the OC sensor we used for the detection of subjects with advanced adenomas was in the lower range than in studies using (8,10,30).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…These studies have used different types of FIT. This hampers a direct comparison of test results because the different types of FIT are known to vary considerably in sensitivity, from 25% to 72%, within the same population (8). Overall, the sensitivity of the OC sensor we used for the detection of subjects with advanced adenomas was in the lower range than in studies using (8,10,30).…”
Section: Discussionmentioning
confidence: 66%
“…Randomized trials have reported that screening using FOBT and sigmoidoscopy may reduce CRC mortality by 15% to 17% (4,5) and 31% (6), respectively. Test performance of the semiquantitative FIT appears to be superior to that of the guaiac-based FOBTs (7,8), but so far, results of randomized controlled trials on the effects of FIT on CRC mortality are lacking. Although many studies assessed the individual performance of FIT or sigmoidoscopy in various populations, only a few were conducted comparing both methods with colonoscopy as a reference standard in screening populations (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Die SensitivitĂ€t und SpezifitĂ€t von in Deutschland verfĂŒgbaren iFOBT variiert deutlich, so dass der generelle Einsatz aller iFOBT nicht empfohlen werden kann [141]. Es erscheint vielmehr erforderlich, dass fĂŒr jeden iFOBT, der fĂŒr die KrebsfrĂŒherkennung eingesetzt werden soll, individuell eine ausreichend hohe SensitivitĂ€t und vor allem SpezifitĂ€t nachgewiesen wird.…”
Section: Level Of Evidence 3aunclassified
“…In screening tests, individuals with a positive fecal immunological test (FIT) are referred for colonoscopy (gold standard). However, performance of this test is suboptimal, with sensitivity for CRC and advanced adenomas of 66-87% and 27-38%, respectively, depending on cut-off value used [45][46][47][48]. In addition, screening with FIT results in a substantial number of false positive tests, and as a consequence, unneeded colonoscopies.…”
Section: Colorectal Cancermentioning
confidence: 99%